Analisis Pengaruh Komunikasi Internal Komitmen Organisasi dan Budaya Organisasi Terhadap Kinerja Pegawai Pada Kantor Dinas Kesehatan Kabupaten Alor - Christofel M. Hiuw (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to determine the effect of Internal Communication Organizational Commitment and Organizational Culture on Employee Performance at the Alor District Health Office. This type of research is quantitative research with data collection techniques namely observation, interviews, and documentation studies. This study uses population primary data and the sample is employees at the Alor District Health Office, totaling 75 people. And the sampling technique in this study is a saturated sample. The statistical method used in this study is multiple linear regression. The results of this study indicate that: (1). partially the internal communication variable has a significance value of 0.000 or 0.0% where this value is smaller than the alpha value of 0.05 or 5% so that the results of this study accept H1 which states that the internal communication variable partially has a positive effect on employee performance at employee at the Alor District Health Office. (2). partially the organizational commitment variable has a significant value of 0.000 or 0.0% where this value is smaller than the alpha value of 0.05 or 5% so that the results of this study accept H2 which states that the organizational commitment variable partially has a positive effect on employee performance at Alor Regency Health Office (3). partially the organizational culture variable has a significant value of 0.001 or 0.1% where this value is smaller than the alpha value of 0.05 or 5% so that the results of this study accept H3 which states that organizational culture variables partially have a positive effect on employee performance at the Office Alor District Health Office. (4). simultaneously the variables of internal communication, organizational commitment and organizational culture affect the performance of Alor Regency Health Office Employees. This type of research has a significant value of 0.000 or 0.00% where this value is smaller than the alpha value which is equal to 0.05 which is 5% so The results of this study simultaneously received H4 which stated that the variables of internal communication, organizational commitment and organizational culture had an effect on the performance of staff at the Alor District Health Office Office. (5). The magnitude of the influence of the variables of internal communication, organizational commitment and organizational culture have an effect on the performance of employees of the Health Service Office of Alor Regency, this type of research is 70.2%, this study simultaneously received H5.